Istikhdām Kitāb al-`Arabiyyah Baina Yaday Aulādinā Bi aṭ-Ṭarīqah al-Mubāsyarah Li Tarqiyah Qudrah aṭ-Ṭalabah `Alā Mahārah al-Kalām (Dirāsah Ijrā’iyyah Bi MAN 4 Aceh Utara): (MAN 4 Aceh Utara دراسة إجرائية بـــــ) استخدام كتاب العربية بين يدي أولادنا بالطريقة المباشرة لترقية قدرة الطلبة على مهارة الكلام - Al Fadil Muhammad; Ahmad Fauzi (EL-MAQALAH : Journal of Arabic Language Teaching and Linguistics, 2021)
MAN 4 Aceh Utara students learn a variety of subjects, including lessons to speak Arabic (Kalam). This lesson aims to make students able to speak Arabic properly and correctly. However, in practice, students face many problems and difficulties in Arabic resulting in the learning outcomes that have not reached the cut score (KKM). One of the reasons is that the teacher has not applied a good method and is in accordance with the student's condition, nor is there suitable learning media in learning. Researchers assume that the direct method and Arabiyah Baina Yadai Auladina textbooks can improve the skills of students in speaking. Therefore, Researchers examine the use of Arabiyah Baina Yadai Auladina textbooks with a direct method to increase skills in Arabic speaking (Classroom Action Research in MAN 4 Aceh Utara). The purpose of the research is to determine the implementation of Arabiyah Baina Yadai Auladina textbooks and direct methods to improve the skills of students in Arabic speaking and its effect on students and student responses to this learning. Classroom action research methods are used in this study. Researchers collected data using observations, questionnaires, and tests. Student of first grade who became the subject of research with the 20 students. The results show indicate that the implementation of learning is in accordance with the plan with a percentage of 57.69% (enough) in the first cycle and increased in the second cycle to 92.3% (very good). The ability of students in Arabic speaking increases after the application of this book and method. This is evident from the average score in the first cycle is 57.75 (enough) and in the second cycle increased is 79.25 (very good). The level of improvement in students' abilities or N-GAIN 1.03 is in the high interpretation. And finally, student's responses to this application were positive.